2023
DOI: 10.1101/2023.10.16.562587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

T cells Use Focal Adhesions to Pull Themselves Through Confined Environments

Alexia Caillier,
David Oleksyn,
Deborah J. Fowell
et al.

Abstract: Immune cells are highly dynamic and able to migrate through environments with diverse biochemical and mechanical composition. Their migration has classically been defined as amoeboid under the assumption that it is integrin-independent. Here we show that activated primary Th1 T cells require both confinement and extracellular matrix protein to migrate efficiently. This migration is mediated through small and dynamic focal adhesions that are composed of the same proteins associated with canonical mesenchymal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
1
2
0
Order By: Relevance
“…Our results indicate that we can push adherent blebby T cells into a highly migratory phenotype by increasing their contractility and fine-tuning their cortical stiffness to intermediate values. This mode of migration is consistent with a recent study that shows that T cells push and pull on the extracellular matrix and require adhesion-based forces to migrate through in vitro systems (120). It is also consistent with another cell migration study, where recruitment of the branched actin nucleator Arp2/3 frequently follows membrane-cortex detachment, depletion of the ERM membrane-cortex linker ezrin and protrusion expansion (92).…”
Section: Rapid Cell Migration Is Potentially Enabled By a Hybrid Bleb...supporting
confidence: 91%
“…Our results indicate that we can push adherent blebby T cells into a highly migratory phenotype by increasing their contractility and fine-tuning their cortical stiffness to intermediate values. This mode of migration is consistent with a recent study that shows that T cells push and pull on the extracellular matrix and require adhesion-based forces to migrate through in vitro systems (120). It is also consistent with another cell migration study, where recruitment of the branched actin nucleator Arp2/3 frequently follows membrane-cortex detachment, depletion of the ERM membrane-cortex linker ezrin and protrusion expansion (92).…”
Section: Rapid Cell Migration Is Potentially Enabled By a Hybrid Bleb...supporting
confidence: 91%
“…The interplay between cells and footprint may be relevant in collective cell migration, where leader cells can pave the way for other cells to follow in their traces. This idea has recently been validated in in vitro experiments in which it has been observed that immune Th1 T cells show a preference for following the tracks that other T cells leave on the ECM (54).…”
Section: R a F Tmentioning
confidence: 88%
“…Human bronchial epithelial cells plated under matrigel showed oscillatory motion as they slowly expanded their explored regions by interactively weakening and carving the ECM (53). Similarly, Th1 T cells deposited on polyacrylamide gels, when covered with agarose gel, migrated along a trajectory, expanding it with each pass as they moved back and forth (54). These findings suggest that the migration modes described here are not necessarily unique to our proposed mechanism or the particular experimental setup of (15) but may arise more generally from how cells make their way through modifying and responding to their environment.…”
Section: R a F Tmentioning
confidence: 99%